Management Policy for Oil and Gas Sector of Bojonegoro Regency Government in Kang Yoto Era - Agus Danugroho; Fitria Yusfira (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2023)
This study aims to understand policy strategies employed by the "Kang Yoto" Government in managing oil and gas sector and its implications for economic resilience of Bojonegoro Regency. The changes in economic resilience after being led by Regent Kang Yoto as well as its relation to management of oil and gas sector is an interesting topic to be investigated. Based on the VOSViewer software, there is a limited amount of analysis conducted on oil and gas management regulations. Therefore, this study employs policy-making theory within the decentralization framework using descriptive qualitative analysis with the assistance of NVIVO 12 Plus data software. The results show that the realization of economic resilience during Kang Yoto era is achieved through the issuance of Regional Regulation Number 23 of 2011. Furthermore, the transparency and accountability of the Local Government are identified as the main factors contributing to the increase in regional economy. This demonstrates the interconnectedness between oil and gas management, as well as the implemented regulations.Keywords: Bojonegoro Oil and Gas, Regional Autonomy, Economic Resilience, Kang Yoto Era AbstrakKajian ini bertujuan untuk memahami strategi kebijakan yang dilakukan oleh Pemerintahan “Kang Yoto” dalam mengelola sektor migas dan implikasinya terhadap ketahanan ekonomi Kabupaten Bojonegoro. Perubahan ketahanan ekonomi setelah dipimpin oleh Bupati Kang Yoto serta kaitannya dengan pengelolaan sektor migas menjadi topik yang menarik untuk ditelaah. Berdasarkan perangkat lunak VOSViewer, terdapat sedikit analisis yang dilakukan terhadap peraturan pengelolaan minyak dan gas. Oleh karena itu, penelitian ini menggunakan teori pembuatan kebijakan dalam kerangka desentralisasi dengan menggunakan analisis kualitatif deskriptif dengan bantuan perangkat lunak data NVIVO 12 Plus. Hasil penelitian menunjukkan bahwa perwujudan ketahanan ekonomi pada era Kang Yoto dicapai melalui penerbitan Peraturan Daerah Nomor 23 Tahun 2011. Selanjutnya, transparansi dan akuntabilitas Pemerintah Daerah diidentifikasi sebagai faktor utama yang berkontribusi terhadap peningkatan perekonomian daerah. Hal ini menunjukkan keterkaitan antara pengelolaan migas, serta peraturan yang berlaku.Kata Kunci: Migas Bojonegoro, Otonomi Daerah, Ketahanan Ekonomi, Kang Yoto.